Химия: большой справочник для школьников и поступающих в вузы / Е. А. Алферова, Н. С. Ахметов, Н. В. Богомолова и др. - Алферова Е. А. (Дрофа, 1999)
Экземпляры: ЧЗ (20181009) / Инвентарный номер: 38064 / Цена: 114.51 / Сис.шифр: 24 / Авт.знак: Х 46 / ГРНТИ: 31 / ББК: 24 я22